The Correlation Of Left Ventricular Strain Analysis And Mitral Annular Disjunction With Ventricular Dysrhythmia In Patients With Mitral Valve Prolapse (Journal of Pharmaceutical Negative Results, 2023)
Objectives: to assess patients with mitral valve prolapse (MVP) presenting with palpitation who have ventricular arrhythmias (VA) versus those without VA by speckle tracking echocardiography to compare the left ventricular longitudinal strain pattern and mitral annular disjunction in correlation with the risk of VA.Methods: This is a cross sectional observational study conducted on 63 patients (37 females and 29 males) with MVP presented with palpitation, who were divided into two groups: Group 1 (Arrhythmic) patients with ventricular arrhythmias and Group 2 (Non-Arrhythmic) patients without. All have detailed electrocardiographic and cardiac rhythm evaluation by Holter monitoring, and complete echocardiographic evaluation including speckle tracking technique.Results: Ventricular arrhythmias presented in 32 out of 63 patients. Where Ventricular Bigeminy represented 81.3%, Non sustained VT 46.9%, Ventricular Trigeminy 25.0%, Frequent VE 21.9%, and Sustained VT 6.3%. There were no significant differences in the grading of MVP and MR, in LV systolic and diastolic functions, and in LV Global Longitudinal Strain (GLS) between the two groups. However, the degree of mitral annular disjunction (MAD) was found to be significantly higher in patients with VA compared to non-arrhythmic patients (6.13±3.26 vs 2.26±2.46, P<0.001). There were no significant differences among LV segmental strains between both groups apart from basal inferior segmental strain which was significantly lower in patients with VA compared to non-arrhythmic patients (-16.38±4.80 vs -18.90±4.50, P=0.036).Conclusions: This study found that in patients with MVP presenting with palpitation, there were higher MAD and lower basal inferior segmental strain in patients with ventricular arrhythmias compared to those without arrhythmias, whereas there was no difference in GLS.